Estimating p-y curves for clays by CPTU method : framework and empirical study - Li, Hongjiang (2020)
Despite its wide use as a tool in foundation design, the piezocone penetration test (CPTU) has been rarely recommended to work for design and analysis of laterally loaded piles. Obtaining lateral response of pile foundations is a complicated engineering problem, especially in nonhomogeneous soils. This paper presents a review of the relationship between the piezocone test and the bearing response of laterally loaded piles and introduces a framework for estimating p-y curves for clays directly using CPTU parameters. To validate this method, full-scale lateral load tests of bored piles with corresponding CPTU tests in Jiangsu soil deposits were conducted and data were compared with the predicted results. In addition, case histories were further considered in detail to study the application of the proposed method for different field conditions. The results predicted by the proposed CPTU-based p-y curve agreed relatively well with the measured results. The proposed method can provide a fast and effective design tool that can be applied to clayey soils with full consideration of soil profiles along the pileembedded depth.